11. EVALUATION OF POSTOPERATIVE DELIRIUM AND ASSOCIATED FACTORS AMONG ELDERLY PATIENTS AT SAILT PAUL GENERAL HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the status of postoperative delirium in elderly patients at Sailt Paul General Hospital in 2025 and to identify associated factors.Methods: Cross-sectional study, quantitative research.Results: The incidence of postoperative delirium in elderly patients was 9.6%. Delirium most commonly began on the first day after surgery (59.3%) and on the second day (33.3%). Several risk factors were identified, including advanced age, nutritional status, underlying hypertension, diabetes, duration of surgery, blood loss, quality of healthcare staff care, and the hospital room environment. There was a significant association between advanced age, healthcare staff care, and the hospital room environment with the occurrence of postoperative delirium in elderly patients at Sailt Paul General Hospital in 2025. Specifically, advanced age was associated with an adjusted odds ratio (OR) of 9.6 (95% CI: 2.6-35.1), healthcare staff care with an adjusted OR of 4.9 (95% CI: 1.03-24.3), and the hospital room environment with an adjusted OR of 27.04 (95% CI: 5.3-137).Conclusion: The incidence of postoperative delirium among elderly patients at Sailt Paul General Hospital in 2025 was low. There was an association between advanced age, the quality of healthcare staff care, and the hospital room environment with the occurrence of postoperative delirium in these patients.
Keywords: Delirium; mechanical ventilation; department of anesthesiology and intensive care.